Kebijakan Presiden Vladimir Putin dalam Menjalin Kerjasama Dengan Indonesia - Harini, Setyasih - (Transformasi, 2012)
AbstractThis article explores about foreign policy of President Vladimir Putin. Under a strong leadershipof President Vladimir Putin, the new Russia is gaining in influence through a series of strategicmoves resolving around its geopolitical assets in energy and military. He also wants to changeRussia’s foreign policy. Ideological fundament-communism and class struggle no longer exist asa significant factor in Russian foreign policy; instead some pragmatist ways can be seen inforeign policy concepts and actions. Putin emphasized his pragmatism in foreign policy in most ofhis speeches and realized it in foreign policy actions. In views of Russia, Indonesia is a countrythat have a lot of potential. In addition to being in the path of international trade, Indonesia hasmany natural resources. So it is important for Russia to make a good cooperation with Indonesia.One of this way is cooperating with Indonesia in economic, political and military. Russia makesIndonesia as a market for the military products, where to invest and make loans. Russia alsosupport Indonesia in dealing with terrorism and other political issues.Keywords: Foreign Policy, Cooperating